Developing bioinformatics tools for the study of alternative splicing in eukaryotic genes - Lim, Yun Ping (2008)
Alternative splicing (AS) is a process that produces more than one protein isoform per gene in eukaryotes. It accounts for huge protein diversity in eukaryotic cells. Consequently, comprehensive studies on AS is of critical importance in cell biology.